The Perceived quality assessment of the health services offered to riverine communities in Brazilian Amazon - Mariosa, Duarcides; Mariosa, Pedro; Falsarella, Orandi; Ferraz, Renato; Pereira, Henrique (International Journal for Innovation Education and Research, 2020)
In line with the UN Agenda 2030 Sustainable Development Goals, Public Health Policies follow in Brazil criteria of universality, completeness, and equity formulated to ensure access to health services in adequate quantity and quality for the entire population. To evaluate the quality of services provided in health units, it is essential, however, to make methodological considerations to concern the use of proper instruments and techniques to achieve accuracy and precision regarding their effectiveness for the user population. Mainly where health care is precarious or in need of adjustment, properly constructed indicators can become excellent management tools. This paper aims to analyze the specificities of the perception of the quality of health services offered to residents of the riverside communities of the Tupé Sustainable Development Reserve (SDR), Manaus, Amazonas, Brazil. The methodological approach is from a descriptive and ecological case study, based on field research with original data collection of fixed residents, aged over 18 years, by applying structured questionnaires and analyzing the results according to the SERVQUAL methodology. In the present study, it observed the impact of previous experiences of attending on the quality of health service. In the case of SDR of Tupé, there were positive evaluations with above 70% in all items. Still, when analyzing the data set and cut, considering the existence or not of previous experience, a different pattern of perception was detected. Based on these results, we suggest that the quality perception of health has to do with competitiveness, associated with the performance standard on the offer available to the customer.